Networked : a contemporary history of news in transition - Russell, Adrienne (Polity Press, 2011)
The contemporary death and life of journalism is the story of an historic cultural transition. We have lived through the end of the mass-media era and the beginning of the networked-media era. We took in news one way for a century and we simply don't do it like that anymore. 'Networked' examines this moment in journalism.